2016
DOI: 10.1126/science.aaf1420
|View full text |Cite
|
Sign up to set email alerts
|

A global genetic interaction network maps a wiring diagram of cellular function

Abstract: We generated a global genetic interaction network for Saccharomyces cerevisiae, constructing over 23 million double mutants, identifying ~550,000 negative and ~350,000 positive genetic interactions. This comprehensive network maps genetic interactions for essential gene pairs, highlighting essential genes as densely connected hubs. Genetic interaction profiles enabled assembly of a hierarchical model of cell function, including modules corresponding to protein complexes and pathways, biological processes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

109
1,649
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,144 publications
(1,764 citation statements)
references
References 120 publications
109
1,649
5
1
Order By: Relevance
“…This suggests that there are additional cellular responses that can take care of defects arising due to jjj1Δ, but are not part of the basal response to the deletion. We checked for the negative genetic interactors of jjj1Δ and found that one of the transcription factors responsible for oxidative stress response are among the top ten ( Figure 5B) (26,33). This led us to hypothesize, that a specific branch of oxidative response work in parallel with jjj1, upregulation of this pathway should lead to abrogation of the fitness defect of jjj1Δ.…”
Section: Cryptic Optimal Pathways Can Be Activated To Alleviate Pqc Dmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that there are additional cellular responses that can take care of defects arising due to jjj1Δ, but are not part of the basal response to the deletion. We checked for the negative genetic interactors of jjj1Δ and found that one of the transcription factors responsible for oxidative stress response are among the top ten ( Figure 5B) (26,33). This led us to hypothesize, that a specific branch of oxidative response work in parallel with jjj1, upregulation of this pathway should lead to abrogation of the fitness defect of jjj1Δ.…”
Section: Cryptic Optimal Pathways Can Be Activated To Alleviate Pqc Dmentioning
confidence: 99%
“…Genetic interactions as obtained through fitness epistasis scores (ε) (26) define functional relationships between pathways; we asked if cellular response is commensurate with epistatic interactions. When not peer-reviewed) is the author/funder.…”
Section: Cellular Response To Pn Perturbation Is Not Guided By Genetimentioning
confidence: 99%
See 2 more Smart Citations
“…In yeast, large-scale studies have begun to define gene interaction networks. 98,99 In mice and humans, a combination of empirical evidence and literature review has begun to define the circuitry of networks associated with disease. 100,101 In many species, modifier genes are readily identified for both simple and complex traits.…”
mentioning
confidence: 99%